2021
DOI: 10.1108/ejtd-10-2020-0145
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relationships among managerial coaching, perceived organizational support, and job engagement in the US higher education context

Abstract: Purpose The purpose of this study was to apply social exchange and organizational support theories to examine the relationship between mid-level strategic enrollment managers’ perceptions of managerial coaching behaviors enacted by their senior managers and their own reported job engagement, as mediated by perceived organizational support (POS) within the US higher education context. Design/methodology/approach A quantitative survey-based half-longitudinal design, which used the latent marker variable techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 87 publications
0
12
0
1
Order By: Relevance
“…Many studies that have explored the relationships between managers who serve as coaches and their subordinates (Adele et al, 2022; Carrell et al, 2021; Kim & Kuo, 2015; McCarthy & Milner, 2013; Milner et al, 2018) point to the positive value of the MAC process (Adele et al, 2022) in improving learning outcomes (Lyons & Bandura, 2022), helping managers adjust their organizational culture to the MAC process (Milner et al, 2020), and enhancing employee performance and work attitudes (Kim et al, 2013).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies that have explored the relationships between managers who serve as coaches and their subordinates (Adele et al, 2022; Carrell et al, 2021; Kim & Kuo, 2015; McCarthy & Milner, 2013; Milner et al, 2018) point to the positive value of the MAC process (Adele et al, 2022) in improving learning outcomes (Lyons & Bandura, 2022), helping managers adjust their organizational culture to the MAC process (Milner et al, 2020), and enhancing employee performance and work attitudes (Kim et al, 2013).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Graham et al (1994) noted that the MAC practice is a popular tool for managers in organizations, and Ali and Aziz (2018) confirmed that its popularity is growing, especially in the Western world. The perceptions toward the MAC practice in organizations are usually positive (Ladyshewsky, 2010); it is cheap, simple and can strengthen the relationship between managers and subordinates (Parsloe, 1999), as well as contribute to the personal and organizational development of coaches (Adele et al, 2022) and foster job engagement among their subordinates (Carrell et al, 2021). However, it also has many known limitations and pitfalls (Tabarovsky, 2015) due to the power gap between the coaches and the coachees (Ladyshewsky, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Emotional engagement pertains to the effort an employee is willing to put forth into applying their personal values, such as beliefs and knowledge, toward their work context (Shuck & Reio, 2011). Research indicates that perception can be influenced by the emotional aspect of employee engagement research (Carrell et al, 2021).…”
Section: Literature Review Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…SET was the theoretical underpinning selected for this study because it has been used in a number of studies on managerial coaching and is considered an appropriate theoretical lens for doing so (Carrell et al , 2021; DuPlessis et al , 2021; Hagen and Williams, 2019; Kim and Kuo, 2015). Emerson (1976) is considered to be one of the seminal founders of SET.…”
Section: Review Of the Literature And Theoretical Underpinningmentioning
confidence: 99%